2019
DOI: 10.36348/sb.2019.v05i11.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Media on Tourists' Destination Selection Decision

Abstract: Social media are interactive communication platform usually used for community-based inputs, content sharing, interaction and collaboration among people. Prominent social media platforms are, facebook, twitter, google+, wikipedia, LinkedIn etc. These social media channels serve as source of information and influence in decision-making process. Travel experience, photos, videos and other contents shared on social media may influence other prospective tourists in their destination selection decision. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Communication on social networks The oldest Internet communication tool is communication via websites and electronic mail (Paul et al, 2019). The problem with communication via the Internet and social media compared to conventional communication channels is the continuous and very rapid evolution of technology and changes in trends and tactics that need to be implemented as quickly as possible in corporate marketing (Gretzel et al, 2008;Buhalis & Law, 2008;Buhalis, 1998).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Communication on social networks The oldest Internet communication tool is communication via websites and electronic mail (Paul et al, 2019). The problem with communication via the Internet and social media compared to conventional communication channels is the continuous and very rapid evolution of technology and changes in trends and tactics that need to be implemented as quickly as possible in corporate marketing (Gretzel et al, 2008;Buhalis & Law, 2008;Buhalis, 1998).…”
Section: 2mentioning
confidence: 99%
“…The conclusions from this study, conducted with users of social networks, will contribute to further research of the theory and the application of recommendations in practice. Unlike the studies by Gupta (2019) and Paul et al (2019), this work examined the decisionmaking process with quantitative data, as suggested by , due to the limited scales available.…”
Section: Theoretical Implicationmentioning
confidence: 99%
“…Uysal, Perdue and Sirgy [36] noted that many tourists consider social networks as a reliable source of information that could help them search and plan their journey, primarily due to the fact that materials accessed through social networks present the current state of the destination that interests them. Through social media platforms, social media users can find essential information about the desired destination [36,37]. These conclusions lead us to the assumption of the third hypothesis: Hypothesis 3 (H3).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Other scholars, such as Hudson and Thal (2013), Shyle and Panajoti (2015) and Amaro, Duarte, and Henriques (2016), found that information on social media sites has the potential to significantly influence travellers’ trip planning. The influence of social media on tourists’ selection of accommodation, food and beverages and shopping behaviours has garnered scholarly attention (Paul, Roy, & Mia, 2019). However, although nightlife entertainment has substantially contributed to cities’ economic development (Calvo, Nofre, & Geraldes, 2017; Homan, 2019; Ross-Houle & Quigg, 2019), research concerning the influence of social media on tourists’ entertainment consumption seems to be less common.…”
Section: Introductionmentioning
confidence: 99%